If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 + -4x = 23x + 20 Reorder the terms: 83 + -4x = 20 + 23x Solving 83 + -4x = 20 + 23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23x' to each side of the equation. 83 + -4x + -23x = 20 + 23x + -23x Combine like terms: -4x + -23x = -27x 83 + -27x = 20 + 23x + -23x Combine like terms: 23x + -23x = 0 83 + -27x = 20 + 0 83 + -27x = 20 Add '-83' to each side of the equation. 83 + -83 + -27x = 20 + -83 Combine like terms: 83 + -83 = 0 0 + -27x = 20 + -83 -27x = 20 + -83 Combine like terms: 20 + -83 = -63 -27x = -63 Divide each side by '-27'. x = 2.333333333 Simplifying x = 2.333333333
| 7-7x=82-42x | | =20+3 | | h-6j+7h+10j= | | 3.2q-3.6-4.1q=1.9q-4.8 | | 4x+27=72-2x | | 6x+39=14x-25 | | 6x^2+49-45=0 | | 3[x-5]=9 | | 25x^2=-32 | | p+10p-5-3p= | | 136-2x=34x+24 | | 6y-2(y+4)=12 | | y+11=4x | | 10+15m-6m-2m= | | 123-6x=2x+11 | | 28x-X^2=192 | | x^2*x=y | | 5-3t=6t-22 | | 52-4x=23x+16 | | 4y+4=3x | | 8p-9=-2p+7 | | 0.3(x+20)-0.05(x-10)=14 | | 6x-29=31 | | (5r-1)(6r-3)= | | 7x+9+5x=-3x+14 | | t+38=7t+8 | | 2y=x-7 | | 3x-5=11x-29 | | 8+27x+6-14x=5+10x+9+3x | | t-47=-35 | | 9p+13=3p-5 | | 3t-47=-35 |